Photocatalytic efficiency of iron oxide nanoparticles for the degradation of priority pollutant anthracene. Issue 1 (2nd January 2017) - Gupta, Himanshu; Kumar, Rahul; Park, Hyun-Sung; Jeon, Byong-Hun
Abstract: The present work demonstrates an efficient and cost effective methodology for the synthesis of iron oxide nanoparticles without the assistance of any capping agent. Two different forms of iron oxide nanoparticles, namely, goethite (α-FeOOH) and magnetite (Fe3 O4 ) were synthesized and characterized through X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM). The XRD spectra were found concordant with JCPDS-ICDD data. The crystallite sizes for goethite and magnetite were found to be 9.85 and 14.13 nm, respectively. The mean particle sizes estimated via SEM analysis were 32.23 and 63.27 nm, respectively. Energy-dispersive X-ray (EDX) spectroscopy was used to estimate the elemental composition of the synthesized nanoparticles (NPs). The NPs were further used for the degradation of anthracene in the presence of UV light. The decay profiles of anthracene, a polycyclic aromatic hydrocarbon listed as a priority pollutant by United States Environmental Protection Agency (USEPA), were investigated with different forms of iron oxides NPs under UV irradiation at ambient temperature. Both forms of iron oxides were efficient for the photodegradation of anthracene. The decay profiles in both the cases followed the first-order kinetics. The half-lives for anthracene degradation were 3.21 and 4.39 h with α-FeOOH and Fe3 O4, respectively. The results reveal that the photocatalytic activity of magnetite is low as compared to goethite.